Implementasi Tugas dan Fungsi Pengawas Madrasah Melalui Supervisi Akademik di MIN 1 Tidore - Rajak, Rahma Abd; Pramono, Aji Joko Budi (Peneliti.net, 2024)
This study aims to examine the implementation of madrasah supervisors' duties and functions through academic supervision at MIN 1 Tidore. Using a descriptive qualitative method with a case study design, this research involved madrasah supervisors, principals, and teachers as informants. Data were collected through in-depth interviews, participant observation, and document analysis. The results show that academic supervision has been implemented systematically with a collaborative approach, but still faces challenges such as time constraints, geographical conditions, and suboptimal follow-up. Nevertheless, academic supervision has had a positive impact on improving teacher competence and the quality of learning. This study recommends developing more adaptive supervision strategies, increasing the intensity of supervision, and strengthening follow-up systems to optimize the impact of academic supervision in madrasahs, especially in archipelagic areas